Expression of Wnt3a, Wnt10b, β-catenin and DKK1 in periodontium during orthodontic tooth movement in rats. (2nd April 2016) - Lu, Juan; Duan, Yingying; Zhang, Miaomiao; Wu, Mingming; Wang, Ying
Abstract: Objective : To investigate the expression of Wnt3a, Wnt10b, β -catenin and DKK1 in the periodontal ligament (PDL) during orthodontic tooth movement (OTM) in rats. Materials and methods : Nickel-titanium closed-coil springs were used to deliver an initial 50 g mesial force to the left maxillary first molars in 30 rats. The force was kept constant for 1, 3, 5, 7, 10 and 14 days until the animals were sacrificed. The right maxillary molars without force application served as control. Paraffin-embedded sections of the upper jaws were prepared for histological and immunohistochemical analyses to detect Wnt3a, Wnt10b, β -catenin and DKK1 expression in PDL. Results : Wnt3a, Wnt10b, β -catenin and DKK1 were expressed on both the ipsilateral and contralateral sides of PDL in each group. After the application of orthodontic force, the expression of β -catenin and DKK1 was initially increased and then decreased on both sides, with maximal levels of expression at day 7 and day 10, respectively. On the compression side, Wnt3a and Wnt10b levels started to increase at day 5, while on the tension side, these two molecules began to increase at day 1. Furthermore, the expression levels of Wnt3a, Wnt10b, and β -catenin were much stronger on the tension side than on the compression side at any of the observation points, while DKK1 level was much higher on the compression side. Conclusion : Wnt3a, Wnt10b, β -catenin and DKK1 expression may be related to the periodontal tissue remodeling following the application of an orthodontic force in rats. These observations suggest that the Wnt/ β -catenin signaling pathway may play a crucial role in periodontal tissue remodeling during OTM.